27‐2: Invited Paper: Correlation of Accelerated Aging to In‐Device Lifetime of Quantum Dot Enhancement Film. Issue 1 (May 2016) - Thielen, James; Lamb, Dave; Lemon, Abby; Tibbits, Josh; Derlofske, John Van; Nelson, Eric
Abstract : Quantum dots are increasingly used in displays to achieve high color gamut at high efficiency. This paper describes the impact of quantum dot lifetime on long‐term display performance and the methods used for predicting in‐device lifetime from accelerated aging results. Test methods are described which give confidence in aging predictions.